Access, equity and costs of induced abortion services in Australia: a cross‐sectional study. (22nd January 2017) - Shankar, Mridula; Black, Kirsten I.; Goldstone, Philip; Hussainy, Safeera; Mazza, Danielle; Petersen, Kerry; Lucke, Jayne; Taft, Angela
Abstract: Objectives: To examine access and equity to induced abortion services in Australia, including factors associated with presenting beyond nine weeks gestation. Methods: Cross‐sectional survey of 2, 326 women aged 16+ years attending for an abortion at 14 Dr Marie clinics. Associations with later presentation assessed using multivariate logistic regression. Results: Over a third of eligible women opted for a medical abortion. More than one in 10 (11.2%) stayed overnight. The median Medicare rebated upfront cost of a medical abortion was $560, compared to $470 for a surgical abortion at ≤9 weeks. Beyond 12 weeks, costs rose considerably. More than two‐thirds (68.1%) received financial assistance from one or more sources. Women who travelled ≥4 hours (AdjOR: 3.0, 95%CI 1.2–7.3), had no prior knowledge of the medical option (AdjOR: 2.1, 95%CI 1.4–3.1), had difficulty paying (AdjOR: 1.5, 95%CI 1.2–1.9) and identified as Aboriginal and/or Torres Strait Islander (AdjOR: 2.1, 95%CI 1.2–3.4) were more likely to present ≥9 weeks. Conclusions: Abortion costs are substantial, increase at later gestations, and are a financial strain for many women. Poor knowledge, geographical and financial barriers restrict method choice. Implications for public health: Policy reform should focus on reducing costs and enhancing early access.